Comparative in Vivo Analysis of the Role of the Adventitia and the Endothelium on Arterial Mechanical Function: Relevance for Aortic Counterpulsation. Issue 6 (June 2017) - Bia, Daniel; Zócalo, Yanina; Wray, Sandra; Cabrera-Fischer, Edmundo I.
Purpose: The comparative effect of the intimal and adventitial layers on arterial biomechanics control, in basal and altered conditions, remains to be elucidated. This study aimed (1 ) to characterize the arterial conduit (CF) and buffering (distensibility) function of the iliac arteries in in vivo animals, in which the intimal and adventitial layers were removed; (2 ) to determine the effects of intra-aortic ballon pumping (IABP) on simultaneously de-adventitialized (DA) and de-endothelialized (DE) iliac arteries before and after induced heart failure. Methods: Pressure and diameter signals were measured in the iliac arteries of sheep (n = 7) in which the adventitial and intima layer were removed. Intra-aortic balloon pump (IABP) assistance was used in a control state and after heart failure induction. Results: Both DE and DA determined significant changes in arterial diameter, distensibility and CF. Changes were higher after DA than after DE in terms of distensibility and CF (p<0.05). DA followed by DE (DA + DE) showed significant increases in arterial diameter and CF, accompanied by a decrease in distensibility (p<0.05) with respect to intact arteries. Heart failure induction caused significant hemodynamic changes without modifying the already impaired local biomechanical parameters. Nonsignificant improvements in the biomechanical parameters of DA+ DE iliac arteries were observed during IABP before and after heart failure induction. Conclusions: Biomechanical changes caused by DA of iliac arteries were more important than those observed after DE. The DA + DE arteries showed significant differences with respect to intact arteries and with DA or DE arteries. IABP-related effects on arterial mechanics were absent in DA+ DE arteries.